#Instafame: exploring the endorsement effectiveness of influencers compared to celebrities. Issue 4 (19th May 2022) - Gräve, Jan-Frederik; Bartsch, Fabian
Abstract: A series of three studies explore the endorsement effectiveness of 'macro' influencers compared with 'regular' celebrities. Using multidimensional scaling, we provide evidence of perceptual differences between celebrities and influencers beyond endorser attractiveness, credibility, expertise, and familiarity. We further study conditions in which endorser type is more or less effective in evoking favorable ad-related responses via consumers' inferences of an ad's manipulative intent. The results show that influencer endorsements in social media need to be subtle to achieve greater effectiveness than celebrity endorsements. In contrast, intrusive advertising in social media is more efficient when done in collaboration with celebrities. No significant differences emerge for endorsements in regular ad formats, though endorsements may benefit from higher awareness levels of celebrities. The findings help marketers make better informed choices between celebrity and influencer advertising collaborations.